THE SPACE-TIME COMPRESSION OF INDIGENOUS TOPONYMY: THE CASE OF MAPUCHE TOPONYMY IN CHILEAN NORPATAGONIA. - Salazar, Gonzalo; Riquelme Maulén, Wladimir (Geographical Review)
The classic approach to research on toponymy is limited to a linguistic focus. This reductionism has had a negative impact on the study of the toponymy of intercultural and indigenous territories, as in the case of the northern Patagonia. Based on a two-year ethnographic study in northern Patagonia, this article analyzes the socio-spatial dimension of Mapuche toponymy, through a mixed methodology involving both data collection and analysis, and an ethnographic approach. The article analyzes how these toponyms emerge from a variety of socio-spatial practices and meanings that are not only intertwined, but also involve several social, environmental, and political dimensions. We argue that the study of indigenous toponymy as a space-time compression entails an ontological opening of toponymy based on the process of inhabiting place. In this regard, the paper discusses the importance of understanding indigenous toponymy as a historically situated process.